PERBEDAAN TEKANAN DARAH PADA AKSEPTOR KONTRASEPSI SEBELUM DAN SETELAH PEMAKAIAN KB SUNTIK 1 BULAN - Agustin, Rofeny (Politeknik Kesehatan Kemenkes Bengkulu, 2015)
Increased blood pressure (hypertension) or decreased (hypotension) affecthomeostasis in the body cause interference with the transport system of oxygen, carbon dioxide,and other metabolic outcomes. Hypertension is a cardiovascular disease prevalence andmortalityis quite high, especially in the developed and developing countries. Data Riskedas 2007 theincidence of hypertension in Indonesia reached 31.7%. Meanwhile, the data Bengkulu CityHealth Office incidence of hypertension as much as 30 According to IDHS (2012) the percentageof participants who experienced hypertension injectables is 0.5% of the number of acceptors. Thestudy aimed to determine differences in blood pressure at the injection acceptors before and afterthe use of injectables 1 month. Design research is an analytic survey with cross sectionalapproach. The population is around the injection acceptors in Puskesmas Nusa Indah Bengkuluin 2013 as many as 604 people. The sample totaled 86 acceptors taken by purposive sampling.The data is then processed by univariate and bivariate analysis. From the results of 86 researchnote acceptors injecting 1 month, blood pressure injection acceptors 1 month before and after theuse of injectables has average - average 9,070. Statistical tests obtained p = 0.000 <α = 0.05, thatthere are significant differences between the blood pressure before and after menggukan 1 monthinjectable contraceptive. For health care workers is expected to provide information andeducation to health 1 month injectable contraceptive acceptors.